The Relationship between Obesity and the Incidence of Pre-Eclampsia - Galuh; Sri Inti; Masadi; Hindun Mardiana; Driana Permata (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Preeclampsia and eclampsia are problems in pregnancy that require special attention because preeclampsia is one of the highest causes of death, especially in developing countries. One of the risk factors that cause pre-eclampsia and eclampsia are Overweight and Obesity. This study aimed to determine the relationship between obesity and the incidence of pre-eclampsia in RSUD dr Soeroto Ngawi in 2022. Based on the scope of the study, it was included in the type of quantitative inference. Based on the time of data collection including the type of design used cross-sectional. data sources include the kind of Secondary. The sample of this study was pregnant at dr. Soeroto Ngawi Hospital in March - June 2022. The sampling technique used was Simple Random Sampling. Test analysis Using Spearman Rank. The results showed that most (82.1%) had a BMI of more than > 27. And most (63.2%) had preeclampsia. The results of the analysis test obtained P Value < that is 0.002 < 0.05. There is a relationship between obesity and the incidence of pre-eclampsia in pregnant women. Suggestions for further researching the factors that cause pre-eclampsia.